Sociocultural relevance of the bottle gourd and selected species of Cucurbitaceae family in West Africa - Olufunke O. Fajinmi; Olaoluwa O. Olarewaju; Georgina D. Arthur; Roger M. Coopoosamy; Kuben Naidoo (AOSIS, 2022)
Background: Since time immemorial, humans have devised means to improvise for survival on the planet earth. The environment has been the source of materials for manufacturing objects that have supported human existence. These materials include plants (plant parts and by-products) such as the Cucurbitaceae species. Aim: To discuss bottle gourd and some selected species of Cucurbitaceae in relation to the history, sociocultural and spiritual lives of the West African people. Methodology: A literature search was conducted on electronic databases such as Google Scholar, Google Books, Scopus, and Web of Science. The search was performed using several terms and free text words, combining them in an appropriate manner. The authors further set inclusion and exclusion criteria to screen for relevant articles. Results and discussion: Plants play crucial roles in the global economic, social, cultural, and spiritual stability. Several plant families have especially played a fundamental role(s) in the spiritual and cultural ceremonies, and history of many tribes and communities in Africa. This is because entertainment tools such as rattles, drums, harps, and lutes used during most of these ceremonies are often by-products of plants. This study revealed that Cucurbitaceae family is a spectacular class of plants with such roles. Traditional musical instruments derived from bottle gourd, Telfairia occidentalis and Momordica charantia, form an integral part of the history, spiritual and sociocultural life of some West African communities. Conclusion: The history of some tribes in West Africa is linked to specific Cucurbitaceae species.